Kepemimpinan Ideal dalam Al-Qur’an (Pandangan M. Quraish Shihab dalam Tafsîr Al-Mishbâh̲) - Abdullah, M. Al-Zurzani G.; Nawawi, Abd Muid; Nurbaiti, Nurbaiti (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to analyze the concept of ideal leadership in the Qur'an according to the view of M. Quraish Shihab. According to him, ideal leadership reflects the characteristics of the Prophet Muhammad (saw), which is identified by experts through the search of the Qur'an and Hadith. These characteristics include shiddîq (honest), amânah (trusted), tablîgh (delivering treatises), and fathânah (giving instructions). The research method used is a qualitative approach and a library research approach. Data collection is carried out through verses of the Qur'an using thematic (Maudhû'i), in other words the author tries to find the answer to the Qur'an by collecting verses of the Qur'an which has one goal, namely about ideal leadership. The results of the analysis show that the ideal leadership must have a character like the Prophet Muhammad (PBUH).